(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
For many centuries, the notion of a 'good woman' across nations has been rooted in values such as obedience, sacrifice, patience, silence, and morality. From Sita in Ramayana to Desdemona in Shakespeare's Othello, the definition of a 'good woman' has been her act of suffering, sacrifice and endurance. The history of women can be understood through what Carl Jung calls the collective unconscious (Jung). However, this collective unconscious wasn’t just a matter of the past—it exists even today, though in a different form. Contemporary writers, especially women, have attempted to dismantle the stereotypes associated with women by presenting female protagonists in their works. They have given long-overdue, well-deserved space to women and have shown them as brave, powerful, assertive, defiant, and unapologetically flawed. Despite differences in geography, culture, and personal experiences, women writers across the world are creating a strikingly similar feminist discourse in contemporary literature. This paper examines how Chitra Banerjee Divakaruni (Indo - American), Ottessa Moshfegh (American), Bernardine Evaristo (English), and Margaret Atwood (Canadian), all belonging to different countries, are writing narratives that come together on common themes of female resistance and defiance of patriarchal norms. They have all attempted to bring women to the forefront, proving that an ideal woman is not just someone who conforms to her circumstances but one who chooses her own path and stands up for herself. Through an analysis of selected works, this paper aims to study how these authors, despite belonging to different continents, reflect a shared struggle against gender oppression, challenging conventional representations of womanhood and attempt to create a new idea of femininity.